Kwestia ochrony życia ludzkiego - czyli konieczność uznania miłości do człowieka za podstawę szacunku do naturalnego środowiska - Stanisław Biały (Studia Ecologiae et Bioethicae)
The point of departure for the reflections in this article was the premise that the ecological crisis is the result not only of the degradation of nature, but also comes from the destruction of that environment, which is the spirituality of modern man. the point is that the more and more intensive use of the biosphere causes many unfavorable chemical and biological changes in the natural environment, which not only have their source in the way of thought and acting of man, but also have their effects on these.